Synthesis, characterization and biological evaluation of Pd(ii), Cu(ii), Re(i) and 99mTc(i) thiazole-based complexes. Issue 5 (24th April 2018) - Mašković, Jelena M.; Hatzidimitriou, Antonios; Damjanović, Ana; Stanojković, Tatjana P.; Trifunović, Srećko R.; Geronikaki, Athina A.; Papagiannopoulou, Dionysia
Abstract : Synthesis and evaluation of antitumoral, antiinflammatory or inflammation-targeted properties of Pd(ii ), Cu(ii ), Re(i ), and 99m Tc(i ) thiazole-based complexes is presented. Abstract : A new thiazole-containing multidentate ligand 2-((2-phenylthiazol-4-yl)methylthio)ethanamine, L, was synthesized and used to prepare new complexes of the formula Pd II LCl2 (Pd–L), Cu II L2 Cl2 (Cu–L) and fac -[Re/ 99m Tc I (CO)3 (L)] + (Re/ 99m Tc–L). The ligand L and the metal complexes were characterized spectroscopically. Furthermore, the structures of Re–L and Cu–L were elucidated by X-ray crystallography. Ligand L acts as a bidentate (Nth, S) chelator in Pd–L, as a bidentate (N, S) chelator in Cu–L and as a tridentate (Nth, S, N) chelator in Re–L. The radiotracer 99m Tc–L was synthesized in high yield and characterised by HPLC comparison with the Re–L analog. The synthesized compounds were evaluated for their anti-inflammatory and cytotoxic properties. The compounds exhibited low anti-inflammatory activity with Pd–L showing the highest activity among them. The cytotoxic activity of the ligand and the complexes against several human cancer cell lines (cervical adenocarcinoma HeLa, colorectal adenocarcinoma LS-174T, lung adenocarcinoma A549, breast adenocarcinoma MDA-MB-231 and normal human lung fibroblast cell line MRC-5) was examined using the MTT assay. The complex Cu–L exhibited the highest cytotoxicity and the complex Pd–L showed the best tumor selectivity. The changes in the cell cycle phase distribution were determined by flow cytometry and it was found that ligand L shows the highest apoptotic activity. The biodistribution studies of 99m Tc–L in mice showed fast tissue clearance. Of all the thiazole-containing compounds, the palladium complex appears to be more promising for future efforts.